Metodologi Studi Islam (Perspektif Arkoun Dan Ibrahim M. Abu Rabi) - Najrul Jimatul Rizki; Yurna Yurna; Rima Erviana; Siti Nurafifah; Rubi Babullah (Jurnal Pendidikan Indonesia (JOUPI), 2023)
The Islamic study methodology is an analytical approach that aims to understand and analyze Islamic phenomena using a systematic scientific method. This study aims to present an abstract that describes the important points discussed in the study of Islamic methodology. Arkoun and Ibrahim M. Abu Rabi''s Islamic Studies Methodology is a topic discussed in several articles found. These articles discuss Abu Rabi''s thoughts and views on contemporary Islamic studies and the history of modern Islamic education. Abu Rabi' emphasizes the importance of interaction between subjects and objects in Islamic studies and pays attention to the interconnective approach in the methodology of Islamic studies. Several articles also discuss fundamental values ​​in Islamic studies and the paradigms of contemporary Islamic thought in understanding the relationship between turath and modernity